Design of Robust Fuzzy Mutual MRAS Estimator for Induction Motor - SAIHI, Mihoub; NOUAI, Ahmed; Kouzi, Katia (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2023)
This study concerns the design of Robust Fuzzy Mutual MRAS Estimator for Induction Motor (IM). The presented estimator estimates both the mechanical speed, stator and rotor resistance. To do this, in a first step, the modeling and vector control of induction Motor were presented. In the second step, the design of PI fuzzy logic controller for speed IM regulation was well explained. The performance of suggested algorithm control was illustrated by some simulation results. In the last step, we have proposed Fuzzy Sensorless speed vector control of IM based on Mutuel –MRAS estimator which detects the speed and some key parameter of IM such as stator and rotor resistance. The feature and efficiency of Sensorless speed were shown by simulation results.
Option : Automatic and systems